Maternal and Fetal Outcome in Cases of Preeclampsia and Eclampsia in Tertiary Care Center of Nepal - Lamsal, Manoj; Sharma, Deepanjali; GC, Narayan; Subedi, Jigyasa; KC, Tara; Banu, Hasina; Manandhar, Bekha Laxmi (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Hypertensive disorders of pregnancy includes Gestational Hypertension, Preeclampsia and Eclampsia, Chronic Hypertension and Preeclampsia superimposed in Chronic Hypertension. These condition complicates around 5 to 10 percent of pregnancies and have signiﬁcant contributions on maternal and fetal adverse outcome. This study was done to ﬁnd out the maternal and fetal outcome in cases of Pre-eclampsia and Eclampsia. MATERIAL AND METHODS It was a hospital based cross sectional observational study done in department of Obstetrics and Gynecology of Universal College of Medical Sciences from August 2021 to June 2022. Maternal and fetal outcome in Preeclampsia and eclampsia were studied in 116 cases. RESULTS Incidence of diseases was 5.94%, preeclampsia 33(28.4%), eclampsia 23(19.8%) and severe preeclampsia 60 (57.7%). Adverse maternal outcome were HELLP (Hemolysis, Elevated liver enzyme and Low platelets counts) syndrome 15 (12.93%), Abruption placenta 7(6.03%), need of blood transfusion 20 (17.24%), Pulmonary Oedema 3(2.58%), Post-Partum Hemorrhage 3(2.58%) and one case had maternal death. Total 121 babies were born, 42(36.20%) admitted in NICU, 10(8.26%) were intra uterine fetal death (IUFD), 3 (2.48%) were neonatal death (NND), 10(8.26%) refused treatment and leave against medical advice. Common fetal morbidities were intra uterine growth restriction (IUGR) 29 (23.76%), preterm Low birth weight 22(18.18%), anomalous baby 3(2.48%) and congenital pneumonia 1 (0.83%). CONCLUSION Proper Antenatal care and screening, timely referral and prompt management favoured the outcome in positive way.